2000
DOI: 10.1348/000711200160282
|View full text |Cite
|
Sign up to set email alerts
|

Attachment research in eating disorders

Abstract: Insecure attachment is common in eating disordered populations, with implications for therapy. Further work with refined instruments may clarify whether or not there is a specific association between attachment style and eating disorder subgroup. However, such an association is likely to be complicated and it may be more fruitful to study specific aspects of attachment, rather than global attachment style, in relation to eating disorder behaviour. The transgenerational transmission of attachment is a fruitful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
112
1
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(130 citation statements)
references
References 14 publications
(24 reference statements)
11
112
1
6
Order By: Relevance
“…To date, four systematic literature reviews have sought to synthesise data on this empirical question 6,10,7,11 .…”
Section: Parental Bonding and Eating Disordersmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, four systematic literature reviews have sought to synthesise data on this empirical question 6,10,7,11 .…”
Section: Parental Bonding and Eating Disordersmentioning
confidence: 99%
“…The initial review concluded that, compared to non-clinical controls, those with eating disorders remember both parents as less caring, but only their father as more protective -with this latter finding more common in women with Bulimia Nervosa (BN) 6 . By contrast, an updated review found that clients with eating disorders consistently remember their parents as more controlling and less affectionate than their non-clinical counterparts (so called affectionless control) 11 . Both reviews also find that those with eating disorders encounter separation anxiety and are more likely than controls to be insecurely attached.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Los padres aportan al ambiente no sólo a través de sus prácticas de control de peso [9][10][11][12][13][14] ; actitud ante la comida 15 e insatisfacción con la imagen y el peso 16,17 , sino a través de las formas de relacionarse con sus hijos. Patrones de apego inseguro y escasa elaboración psíquica conjunta de los eventos emocionales predisponen a trastornos de alimentación 18 y autoimagen 19 si utilizan el comer como regulador emocional preferente.…”
unclassified